Failure to see money on a tree: inattentional blindness for objects that guided behavior - Hyman, Ira E.; Sarb, Benjamin A.; Wise-Swanson, Breanne M. (Frontiers in Psychology, 2014)
How is it possible to drive home and have no awareness of the trip? We documented a new form of inattentional blindness in which people fail to become aware of obstacles that had guided their behavior. In our first study, we found that people talking on cell phones while walking waited longer to avoid an obstacle and were less likely to be aware that they had avoided an obstacle than other individual walkers. In our second study, cell phone talkers and texters were less likely to show awareness of money on a tree over the pathway they were traversing. Nonetheless, they managed to avoid walking into the money tree. Perceptual information may be processed in two distinct pathways – one guiding behavior and the other leading to awareness. We observed that people can appropriately use information to guide behavior without awareness.